Directing Curriculum through Standards: A Content Analysis of the 2010 Texas State Social Studies Standards - Smith, Norman Edward (The University of Arizona., 2012)
In 2010 the Texas Education Agency adopted newly rewritten curriculum standards for the state's social studies courses K-12. The period leading up to the adoption of the standards proved contentious as the new standards moved out of the writing committees and into the public realm. The issues brought forth from initial readings of the standards appeared in the national spotlight as educators and the general public from around the country voiced their concerns. Many concerns centered on the belief that the Texas State Board of Education had rewritten the standards to reflect a more politically conservative world view along with an emphasis on traditional Judeo-Christian beliefs. Members of the state board argued that the previous standards reflected a politically liberal world view and that the board needed to bring balance to the standards. Because of national criticism changes were made but on a limited scale. The purpose of this study was to assess if the rewritten standards demonstrated a politically conservative preference as well as an emphasis on Judeo-Christian beliefs. During the analysis I included information regarding a preference for capitalism, a focus on Texas and U.S. history while minimizing world history and a focus on memorization rather than critical thinking. The analysis revealed that the rewritten standards demonstrate a politically conservative leaning while promoting traditional Judeo-Christian beliefs. Analysis and research further revealed that the standards promote capitalism while limiting the study of other economic systems in the world. In regards to the preference for Texas and U.S. history versus world history my analysis confirmed a limited presence of world history; however, research also revealed that this issue is not limited to the state of Texas, but a number of other states in the U.S. Finally, my analysis demonstrated that many of the standards' objectives begin with verbs found on verb lists from Bloom's Taxonomy. By using Bloom's Taxonomy I learned that a majority of objectives throughout the K-12 standards operate in the lower half of the Taxonomy rather than the upper half meaning that there is an emphasis on lower order thinking skills rather than higher order thinking skills.